Fatty Acids/Tetraphenylethylene Conjugates: Hybrid AIEgens for the Preparation of Peptide-Based Supramolecular Gels - Impresari, Elisa; Bossi, Alberto; Lumina, Edoardo Mario; Ortenzi, Marco Aldo; Kothuis, Josine Marie; Cappelletti, Graziella; Maggioni, Daniela; Christodoulou, Michael S.; Bucci, Raffaella; Pellegrino, Sara (Frontiers in Chemistry, 2022)
Aggregation induced emissive materials are gaining particularly attention in the last decades, due to their wide application in different fields, from optical devices to biomedicine. In this work, hybrid compounds composed by tetraphenylethylene scaffold combined with fatty acids of different lengths, were synthesized, and characterized. These molecules were found able to self-assemble in aqueous environment into different supramolecular emissive structures depending on chemical composition and water content. Furthermore, they were used as N-terminus capping agents in the development of peptide-based materials. Finally, the functionalization of a 5-mer laminin derived peptide led to the obtainment of luminescent fibrillary materials that were not cytotoxic and were able to form supramolecular gels in aqueous environment.